In het spoor van Emile Zola. De narratologische code(s) van het Europese naturalisme - Borghart, Pieter (Academia Press, 2006)
For the first time since Chevrels seminal monography Le naturalisme: étude d'un mouvement littéraire international (1982), this study presents an encompassing approach to European naturalism. By means of a logical theoretical framework drawing on both comparative literature and narratology, Pieter Borghart proposes a more nuanced definition of naturalism than those traditionally found in the existing literature. By analyzing naturalism in 19th century Modern Greek literature, the second part of this monography concretely shows how this definition offers fruitful perspectives to reassess literary history.